DESIGN OPTIMIZATION AND EXPERIMENTAL DATA OF LOW ENTHALPY GEOTHERMAL POWER PLANT DESIGN BY USING ORGANIC RANKINE CYCLE - Gaos, Yogi Sirodz; Wicaksono, Muhammad Faisal; Rodiah, Iis (Universitas Ibn Khaldun Bogor, 2016)
A lot of heat energy can be tap to produce electricity by converting the heat and enthalpy to move a steam turbine cycle, or usually known as Rankine Cycle. But steam cycle has to have a high temperature and high enthalpy, so lower temperature and lower enthalpy source such as geothermal brine water, solar thermal, and waste heat gas cannot be tap to produce electricity. These potential belongs to ORC or Organic Rankine Cycle. ORC has no need to utilized high temperature and enthalpy, it can use temperature as low as 80ºC instead of 170ºC or more. By utilizing ORC system, these sources is open to produce electricity. These days a lot of research for ORC is done either by simulation or by experiment and the source is also varied. For this case, the source is geothermal brine water. The design of ORC begins with calculating the overall ORC heat balance using Cycle Tempo. Thus the duty of preheater, evaporator, turbine, condenser, pump, and cooling tower can be obtained. Then using working fluid n-pentane, we calculate and optimized the thermal efficiency. After that, every individual equipment is designed and calculated by using HTRI. Design optimization which had been obtained then used as reference to do the experiment. Unfortunately, the data from the latest experiment showed that the temperature from the geothermal brine water has not met requirement yet. Therefore, further experiment has to be done with some improvement to the system.